The transformation of welfare states? - Ellison, Nicholas, 1952- (Routledge, 2006)
This accessible work provides a 'political sociology' of welfare states in industrial societies, with both historical and contemporary perspectives. Ellison focuses on the social and political underpinnings of a number of welfare regimes and looks at the transformations they have undergone and the challenges they face. This book assesses current debates about the role of 'globalization' in welfare state change, paying particular attention to contemporary views about the capacity of embedded institutional structures to limit the effects of global economic pressures. Ellison assesses the changing.